The relationship between work design and retirement: implications for organizational policy - Griffiths, Amanda; Knight, Alec; Mohd Mahudin, Nor Diana (Gower Publishing Limited, 2012)
In most developed countries the population is ageing. A combination of factors is responsible, although increasing life expectancy and declining birth rates are the primary drivers. National-level initiatives, such as increasing the age at which people can access their pensions, are encouraging later retirement. The upshot of this is that many people, largely for financial reasons, currently find themselves needing to extend their working lives, and to postpone their previously planned retirement. For many people, continuing to work will be an economic necessity; others may wish to continue to work even if not financially compelled to do so. For some, work contributes to a sense of purpose, self-esteem and provides opportunities for engagement; for others it can be tedious, unpleasant and stressful. Some may choose to continue to work not because in itself it provides meaningful activity, but because it funds other activities that hold purpose and enjoyment. Yet others may prefer to work part time in a job that does not hold much excitement, because it affords time to engage in more interesting activities outside work. But the general result will be that over the next few decades, many organizations will see changes in the profile of their workforces, with more workers approaching the transitional phase leading toward retirement.